Tri Hita Karana Based Visionary Leadership in Realizing Harmony Within Educational Institutions in Cluster IV of Kediri District - Putu Dian Handayani; Ida Bagus Putu Arnyana (International Journal of Multidisciplinary Sciences, 2026)
Educational leadership in the twenty first century requires the capacity to cultivate a harmonious, character driven, and sustainable school culture through the integration of local wisdom values. This study aims to examine the implementation of Tri Hita Karana based visionary leadership in fostering school harmony within Cluster IV of Kediri District, Tabanan Regency, Bali. A qualitative descriptive approach was employed in this study. Data were collected through observations, in-depth interviews, and document analysis involving school principals as key informants. The data were analyzed using the interactive model developed by Miles, Huberman, and Saldana, which consists of data condensation, data display, and conclusion drawing and verification. The findings indicate that visionary leadership was manifested through the continuous communication of the school vision, participatory decision-making processes, teacher professional development initiatives, and the implementation of school programs focused on character formation and environmental stewardship. The values of Tri Hita Karana were embodied through religious and spiritual practices (parhyangan), the promotion of mutual cooperation, deliberation, and collaborative relationships among school members (pawongan), as well as environmental conservation programs, regular community service activities, and school environmental management practices (palemahan). These initiatives contributed to the development of spiritual, social, and ecological harmony, as reflected in increased participation in school activities, strengthened interpersonal relationships, and the creation of a clean, orderly, and supportive learning environment. The study concludes that the integration of visionary leadership and Tri Hita Karana values contributes to the development of a harmonious school culture and offers an alternative model of educational leadership grounded in local wisdom for addressing contemporary educational challenges.